ANALISA HUKUM PERTANGGUNG JAWABAN PIDANA DALAM TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA OLEH ANGGOTA POLRI - Ahmad Yunus; Moh. Jeweherul Kalamiah (Lembaga Pengembangan Kinerja Dosen, 2023)
The circulation of narcotics and illegal drugs in Indonesia has disturbed the majority of the public, and almost every day the media shows arrests of illicit traffic of narcotics and other criminal acts. In carrying out their duties as law enforcers the police are guided by the code of ethics as a guideline for daily implementation. Regulations related to the police code of ethics can be seen from Law Number 2 of 2002 concerning the Indonesian National Police, Regulations of the Chief of Police of the Republic of Indonesia Number 8 of 2006 and Number 7 of 2006 Each of them is binding on the implementation of the police's daily duties. This study analyzes law enforcement by the police in Narcotics Crimes committed by members of the National Police and criminal sanctions against members of the National Police who commit Narcotics Crimes. This study uses a normative juridical type, namely by carrying out legal research by looking at the laws and regulations related to Law no. 35 of 2009 concerning Narcotics. After the research material is obtained and collected, the material is then processed and analyzed with legal arguments based on deductive-inductive (general-specific) legal logic. The author can conclude that cases of narcotics settlement carried out by the police are the same as that of the community in general, namely through general courts.